Endodontic management of bilateral mandibular canine with type two canals configuration - Seema Yadav (Wolters Kluwer Medknow Publications, 2015)
Successful endodontic treatment depends upon the clinician's knowledge and ability to manage aberrant anatomy. The mandibular canine normally comprises one canal and one root but 15% may have two canals with one or two foramina and even less frequent may have two roots. This paper presents a case report of bilateral mandibular canine having two root canals which merge into one canal and one foramina.